2008
DOI: 10.1242/jcs.030098
|View full text |Cite
|
Sign up to set email alerts
|

p53 is localized to a sub-nucleolar compartment after proteasomal inhibition in an energy-dependent manner

Abstract: process as reduction of ATP levels prevents nucleolar localization. In addition, p53 sub-nucleolar accumulation is abolished when cells are subjected to various types of genotoxic stress. Furthermore, we show that monoubiquitination of p53, which causes it to localize to the cytoplasm and nucleoplasm, does not prevent the association of p53 with the nucleolus after MG132 treatment. Importantly, we demonstrate that p53 nucleolar association occurs in lung and bladder carcinomas. Journal of Cell Science ATP-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 61 publications
6
24
1
Order By: Relevance
“…TTRAP was previously shown to interact with PML in Y2H and to localize within PML-NBs in transfected cells. 7 As proteins associated with PML-NBs accumulate in the nucleolus upon treatment with high concentration of proteasome inhibitors, 11,12 we proved that TTRAP nucleolar granules were PML-NBs by To confirm that the nucleolar TTRAP is a part of PML-NBs, we tested its physical interaction with PML-IV and PML-NBs component DAXX. Both proteins (Figures 2d and e) were detectable in TTRAP-bound fractions but not in negative controls.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…TTRAP was previously shown to interact with PML in Y2H and to localize within PML-NBs in transfected cells. 7 As proteins associated with PML-NBs accumulate in the nucleolus upon treatment with high concentration of proteasome inhibitors, 11,12 we proved that TTRAP nucleolar granules were PML-NBs by To confirm that the nucleolar TTRAP is a part of PML-NBs, we tested its physical interaction with PML-IV and PML-NBs component DAXX. Both proteins (Figures 2d and e) were detectable in TTRAP-bound fractions but not in negative controls.…”
Section: Resultsmentioning
confidence: 87%
“…In particular, PML itself, Sp100, SUMO-1 and p53 localize to subnucleolar regions in response to high doses of MG132. [11][12][13] We previously showed that treatment of SH-SY5Y neuroblastoma cells with the low concentrations of proteasome inhibitors triggered TTRAP relocalization to the cytoplasm, to form juxtanuclear aggresome-like structures. 8 We thus investigated the cellular localization of PML-NBs-associated protein TTRAP in the cells treated with increasing concentrations of drug.…”
mentioning
confidence: 99%
“…Moreover, many cellular proteins such as p53 (Karni-Schmidt et al, 2008;Klibanov et al, 2001), promyelocytic leukemia gene product (PML) (Mattsson et al, 2001), cyclins, cyclin dependent kinases (CDKs) and several transcription factors such as Sp1 and Sp3 (Latonen et al, 2011) have been shown to accumulate in the nucleolus upon proteasome inhibition.…”
Section: V454 Role Of the Nucleolus In Stress Responsementioning
confidence: 99%
“…This is reminiscent of the action of the nucleolar protein, p14 ARF, that binds and sequesters Mdm2 in the nucleolus in response to oncogenic stress. Elevated levels of p53 protein in nucleoli are observed in response to proteasome inhibition with MG132 [10,11]. The function of p53 in the nucleolus is uncertain but nucleolar localization may facilitate the ability of p53 to repress RNA polymerase 1 activity which is required for synthesis npg of 47S precursor rRNA transcripts that are processed to form 18S, 5.8S and 28S rRNAs [11].…”
mentioning
confidence: 99%
“…Elevated levels of p53 protein in nucleoli are observed in response to proteasome inhibition with MG132 [10,11]. The function of p53 in the nucleolus is uncertain but nucleolar localization may facilitate the ability of p53 to repress RNA polymerase 1 activity which is required for synthesis npg of 47S precursor rRNA transcripts that are processed to form 18S, 5.8S and 28S rRNAs [11]. The importance of def during embryonic development in fish suggests that nucleolar p53 needs to be tightly regulated so that it is available to regulate ribosome biogenesis at times of stress without interfering with normal embryonic development under normal stress-free conditions.…”
mentioning
confidence: 99%